Analisis Sentimen Menggunakan Metode Naive Bayes Pada Komentar Penonton YouTube Windah Basudara - Adam Putra Berlin; Arafat Febriandirza (STIKOM Tunas Bangsa Pematangsiantar, 2025)
The development of social media has provided users with a space to express their opinions through comments, including on the YouTube platform. One content creator who has a large fanbase and active comment section is Windah Basudara. This study aims to analyze the sentiment of viewer comments on one of Windah Basudara’s videos using the Naive Bayes algorithm. This method was chosen due to its effectiveness in text classification and sentiment analysis. The data used consists of comments from the video titled